High-Intensity Interval Training Decreases Muscle Sympathetic Nerve Activity in Men With Essential Hypertension and in Normotensive Controls - Ehlers, Thomas Svare; Sverrisdottir, Yrsa; Bangsbo, Jens; Gunnarsson, Thomas Petursson (Frontiers in Neuroscience, 2020)
Exercise training is a cornerstone in reducing blood pressure (BP) and muscle sympathetic nerve activity (MSNA) in individuals with essential hypertension. High-intensity interval training (HIIT) has been shown to be a time efficient alternative to classical continuous training in lowering BP in essential hypertension, but the effect of HIIT on MSNA levels has never been investigated. Leg MSNA responsiveness to 6 weeks of HIIT was examined in 14 hypertensive men (HYP; age: 62 ± 7 years, night time BP: 136 ± 12/83 ± 8 mmHg, BMI: 28 ± 3 kg/m2), and 10 age-matched normotensive controls (NORM; age: 60 ± 8 years, night time BP: 116 ± 2/68 ± 4 mmHg and BMI: 27 ± 3 kg/m2). Before training, MSNA levels were not different between HYP and NORM (burst frequency (BF): 41.0 ± 10.3 vs. 33.6 ± 10.6 bursts/min and burst incidence (BI): 67.5 ± 19.7 vs. 64.2 ± 17.0 bursts/100 heart beats, respectively). BF decreased (P < 0.05) with training by 13 and 5% in HYP and NORM, respectively, whereas BI decreased by 7% in NORM only, with no difference between groups. Training lowered (P < 0.05) night-time mean arterial- and diastolic BP in HYP only (100 ± 8 vs. 97 ± 5, and 82 ± 6 vs. 79 ± 5 mmHg, respectively). The change in HYP was greater (P < 0.05) compared to NORM. Training reduced (P < 0.05) body mass, visceral fat mass, and fat percentage similarly within- and between groups, with no change in fat free mass. Training increased (P < 0.05) V̇O2-max in NORM only. Six weeks of HIIT lowered resting MSNA levels in age-matched hyper- and normotensive men, which was paralleled by a significant reduction in BP in the hypertensive men.